Therapeutic effects of electrospun chitosan nanofibers on animal skin wounds: A systematic review and meta-analysis - Dalia Isabel Sánchez-Machado; Anahí Maldonado-Cabrera; Jaime López-Cervantes; Blayra Maldonado-Cabrera; Andrés Francisco Chávez-Almanza (Elsevier, 2023)
Electrospun chitosan nanofibers (QSNFs) enhance the healing process by mimicking skin structure and function. The aim of this study was to analyze the therapeutic effects of QSNFs application on animal skin wounds to identify a potential direction for translational research in dermatology. The PRISMA methodology and the PICO scheme were used. A random effects model and mean difference analysis were applied for the meta-analysis. A meta-regression model was constructed, risk of bias was determined, and methodological quality assessment was performed. Of the 2370 articles collected, 54 studies were selected based on the inclusion and exclusion criteria. The wound healing area was used for building models on the 3rd, 7th, and 14th days of follow-up; the results were − 10.4% (95% CI, −18.2% to −2.6%, p = 0.001), −21.0% (95% CI, −27.3% to −14.7%, p = 0.001), and − 14.0% (95% CI, −19.1 to −8.8%, p = 0.001), respectively. Antioxidants and synthetic polymers combined with QSNFs further reduced skin wound areas (p < 0.05). The results show a more efficient reduction in wound area percentages in experimental groups than in control groups, so QSNFs could potentially be applied in translational human medicine research.